PERANAN KEPALA DESA DALAM PARTISIPASI PENGGERAKAN PEMBANGUNAN DI DESA SALIBABU KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - pinggian, Yulia; Mandey, JANTJE; Pombengi, Jericho D (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACKThe implementation of the duties and functions of a village chief in the government isone of the activities of government officials in an effort to improve the welfare of thecommunity, as the purpose of this study is to provide a description of the implementation ofthese functions. The role of village chief is very important in approaching and grow and developself-help mutual aid society in order to realize the implementation of development that has beenplanned in the Budget of the Village.This means that the head of the village as a leader in thevillage is the organizer and the person in charge in the field of governance and communitydevelopment, as well as village chief is responsible for growing and developing self-help mutualaid society. By looking at how important the role of the village head held thus further researchon "The Role of the Village Head In The agitation participation from communities in the VillageDistrict of Salibabu Salibabu Talaud Islands".In this study, the type of research that is in use which is a type of qualitative research,the research focus is the role of the village chief purpose in scaling community participation inrural development. Respondents / instrument in this study is that local officials and villagers ofSalibabu District of Salibabu Talaud Islands as many as 10 people.The researchers' analysis adjusting of some theory is concerned with the studyindicators, namely: first, the role of the village head as a motivator in moving people'sparticipation in village development Salibabu; second, the role of the village head as a facilitatorin moving people's participation in rural development Salibabu; and third, the role of the villagehead as a mobilizer in moving people's participation in rural development Salibabu.Based on the research role of the Village Head of Public Participation In The agitation inthe Village District of Salibabu Salibabu Talaud Islands in view of the three aspects of the roleof the village head as motivators, facilitators and mobilizers suda good but its role inimplementing the village head had to really play its role properly so that the public canparticipate in any program / village development activities. And needs to know that the successof the village head is inseparable from the role of the community he leads.Keywords: Role of the village head, promote community participation